2023
DOI: 10.1503/cjs.012122
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative spinal conditions requiring emergency surgery: an evolving crisis in a publicly funded health care system

Abstract: Background: Surgery for degenerative spine pathologies is typically performed on a scheduled basis; however, worsening symptoms may warrant emergency surgery. An increasing number of patients requiring emergency surgery has been observed (22.6% in 2006 to 34.8% in 2019). We sought to compare the outcomes of patients who received scheduled surgery and those who required emergency surgery. Methods: All patients treated between Jan. 1, 2006, and Dec. 31, 2019, were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The study also demonstrated that spinal degenerative disease were mostly elective admissions through the clinics. This is in tandem with a study done in Canada, USA that showed majority of degenerative spinal conditions were elective cases [ 51 53 ]. This is because they are degenerative conditions are common with advancing age and are usually chronic and non-urgent in nature.…”
Section: Discussionsupporting
confidence: 83%
“…The study also demonstrated that spinal degenerative disease were mostly elective admissions through the clinics. This is in tandem with a study done in Canada, USA that showed majority of degenerative spinal conditions were elective cases [ 51 53 ]. This is because they are degenerative conditions are common with advancing age and are usually chronic and non-urgent in nature.…”
Section: Discussionsupporting
confidence: 83%